ω-substituted alkyl carboxylic acids as antidiabetic and lipid-lowering agents - Meyer, Kirstin; Voss, Edgar; Neidlein, Richard; Kühnle, Hans-Frieder; Pill, Johannes (European journal of medicinal chemistry, 1998)
In screening experiments certain ω-substituted alkyl carboxylic acids, were found to produce an increase in insulin-stimulated 14C-acetate incorporation into triglycerides, which may indicate an improvement in the action of insulin. Antidiabetic and lipid-lowering properties in genetically diabetic ob/ob mice demonstrated the in vivo relevance of the insulin-potentiating effects seen in vitro. The chemical structures of the ω-substituted alkyl carboxylic acids with insulin-potentiating effects correspond to the general formula ring-spacer-COOH. A close structure-activity relationship was observed. The most potent compound in ob/ob mice was 3e, which normalized blood glucose as well as hyperinsulinaemia and lowered serum triglycerides and cholesterol by 52% and 37%, respectively. On the basis of these results, ω-substituted alkyl carboxylic acids are interesting as a new class of oral antidiabetic agents with insulin-sensitizing and lipid-lowering activity.
Elektronische Reproduktion der Druck-Ausgabe 20. Mai 1999
Gesehen am 06.07.2023